Determination of antifungal activity of plant extracts - Lau, Ee Hong (2015)
Fungal disease is considered as one of the current emerging diseases since many fungal pathogens such as Candida albicans can undergo mutation rapidly and resistant to common antifungal agents. Plants are expected to contain natural antimicrobial compounds such as alkaloids, flavonoids, and phenolic compounds to protect themselves from microbial diseases. Thus, plants are one of the potential sources to obtain new antifungal agents. The aim of this study was to determine the antifungal activity of 12 species of plants in Malaysia against Aspergillus niger and Candida albicans. Disc diffusion method was used in this study to assess the antifungal properties of plants and measurement of minimum inhibitory concentration (MIC) was done by resazurin-based microtiter dilution assay. The results showed that all tested plant extracts had no activity against A. niger and only 3 extracts (Coleus amboinicus, Ipomoea aquatica, and Premna cordifolia) exhibited weak antifungal activity against C. albicans. Among them, I. aquatica showed best antifungal activity against C. albicans with 10 mm clearing zone at concentration of 25 mg/mL. The MIC of C. amboinicus, I. aquatica and P. cordifolia were 3.125, 1.56, and 3.125 mg/mL respectively. This study showed that none of the tested plants is a potential source of new antifungal agents since all of them failed to inhibit the growth of tested fungi effectively.